The Lexicon of Development: A Quantitative History of the Language of Development Studies - Absell, Christopher David (Iberoamerican Journal of Development Studies, 2015)
The objective of this article is to examine the history of the language of development theory in order to elucidate the nature of its terminology. The history of the principal terms of development theory (economic/sustainable/human development, Third World, and North/(Global) South) is examined by way of a quantitative study of the frequency of the usage of these terms during the 20th century based on a dataset of millions of digitised books made available by Google Books. The author argues that the results of the study provide empirical evidence that the language of development theory is a historical-ideological construction which is embedded in the structure of the world economy.
Keywords: development theory; language; ngrams